Next‐day residual effects of flibanserin on simulated driving performance in premenopausal women. (31st May 2017) - Kay, Gary G.; Hochadel, Thomas; Sicard, Eric; Natarajan, Karthi K.; Kim, Noel N.
Abstract: Objective: The objective of this study was to determine the next‐day residual effects of acute and steady‐state nighttime dosing of flibanserin on simulated driving performance and cognitive function in healthy premenopausal women. Methods: In this randomized, double‐blind, placebo‐controlled, four‐way crossover study, 72 subjects were treated with either acute oral doses of placebo, zopiclone 7.5 mg (positive control) or flibanserin 100 mg at bedtime (indicated therapeutic dose), or after chronic nightly oral doses of flibanserin 100 mg for 1 week followed by a single bedtime dose of flibanserin 200 mg (supratherapeutic dose). Simulated driving assessments were conducted 9 hr after dosing and cognitive function tests were administered immediately before or during the driving assessment. Results: Zopiclone increased standard deviation of lateral position (≥3.1 cm; p < .0001) relative to placebo and impaired other parameters previously shown to be sensitive to sedation. No impairment was detected for flibanserin at either dose relative to placebo. Flibanserin 200 mg was similar to the 100‐mg dose on cognitive testing and driving performance even though commonly reported adverse events for flibanserin were predictably increased at the higher dose. Conclusions: At both therapeutic and supratherapeutic doses, flibanserin did not impair next‐day driving performance and cognitive function compared to placebo.